Mali : Tenth Review under the Extended Credit Facility Arrangement and Request for Waiver of Nonobservance of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2018)
Mali is a fragile state, struggling with insurgency and making efforts to build peace. The 2013-18 ECF-supported program has broadly succeeded in achieving its objectives under difficult circumstances. The program helped stabilize the economy in the context of persistent insecurity, changing terms of trade, and adverse weather conditions. The economy has continued to perform well in 2018, with robust economic growth and low inflation, but poverty and inequality have remained high. The near-term outlook for sustainable growth is subject to downside risks from unfavorable security conditions.